Pathogen specificity of Treponema pallidum subsp. pallidum integral membrane proteins identified by phase partitioning with Triton X-114. - Radolf, J D (1988)
The antigenically conserved proteins of Treponema pallidum subsp. pallidum and four nonpathogenic cultivatable treponemes were investigated by phase partitioning with the nonionic detergent Triton X-114 and immunoblot analysis. None of the T. pallidum integral membrane proteins identified by phase partitioning (detergent-phase proteins) appeared to be antigenically related to proteins of the nonpathogens. Protease-resistant material similar to lipopolysaccharide was identified in the detergent phase from T. phagedenis biotype Reiter but was not detected in T. pallidum.